Optimization of the parameters of truss beams with two posts - A. K. Yusupov; H. M. Musеlеmov,; T. O. Ustarhanov (Вестник Дагестанского государственного технического университета: Технические науки)
Based on the theoretical results obtained in the article [17], here the analysis of the influence of various design parameters on the own weight and cost of metal of truss beams with two posts is carried out. An optimal parameter has been obtained that makes it possible to reduce the calculated bending moment in the cross section of a truss beam with two struts.Method. By equalizing the bending moments in various design sections of the truss beam, the internal force factors are reduced. The corresponding equation for optimizing the parameters of the beam has been drawn up and a formula has been obtained to determine the optimal parameter of the structure as a whole.Result. Using the example of numerical calculations, a decrease in the calculated bending moment by 14% compared to truss beams without optimization is shown.Conclusion. The proposed method and algorithm testify to the efficiency and rationality of the obtained optimal parameter of the structure as a whole.